Synergistic effects and optimization of nitrogen and phosphorus concentrations on the growth and nutrient uptake of a freshwater Chlorella vulgaris. Issue 1 (2nd January 2017) - Alketife, Ahmed M.; Judd, Simon; Znad, Hussein
ABSTRACT: The synergistic effects and optimization of nitrogen (N) and phosphorus (P) concentrations on the growth of Chlorella vulgaris (CCAP 211/11B, CS-42) and nutrient removal have been investigated under different concentrations of N (0–56 mg/L) and P (0–19 mg/L). The study showed that N/P ratio has a crucial effect on the biomass growth and nutrient removal. When N/P=10, a complete P and N removal was achieved at the end of cultivation with specific growth rate (SGR) of 1 d −1 and biomass concentration of 1.58 g/L. It was also observed that when the N content <2.5 mg/L, the SGR significantly reduced from 1.04 to 0.23 d −1 and the maximum biomass produced was decreased more than three-fold to 0.5 g/L. The Box–Behnken experimental design and response surface method were used to study the effects of the initial concentrations (P, N and C) on P and N removal efficiencies. The optimized P, N and C concentrations supporting 100% removal of both P and N at an SGR of 0.95 were 7, 55 and 10 mg/L respectively, with desirability value of 0.94. The results and analysis obtained could be very useful when applying the microalgae for efficient wastewater treatment and nutrient removal.